(untitled) (CAHIERS MAGELLANES-NS, 2024)
Financial literacy is essential for individual well-being and economic stability. In India, the Reserve Bank of India (RBI) and the Government of India (GoI) has implemented various policies and programs to enhance financial literacy. This paper examines these initiatives and evaluates their impact on financial literacy levels in the country. This research paper provides a detailed analysis of the efforts made by the RBI and the Government of India (GoI) to enhance financial literacy in India, highlighting the policies, programs, and their impacts, and addressing future challenges and directions.